Pengaruh Aromaterapi Lemon Terhadap Mual Muntah Pada Ibu Hamil Trimester I di Wilayah Kerja Puskesmas Bebesan - Selvia Zuhra Putri (Malahayati Nursing Journal, 2024)
ABSTRACT The Effect of Lemon Aromatherapy on Nausea and Vomiting in First Trimester Pregnant Women in the Bebesan Work Area. Emesis gravidarum is nausea and vomiting that appears in the first four weeks of pregnancy and slowly disappears at twelve weeks of pregnancy. Nausea and vomiting are the most common symptoms experienced by pregnant women in the first trimester, these symptoms are experienced by 70-85% of women. To see the effect of lemon aromatherapy on nausea and vomiting in first trimester pregnant women in the Bebesan work area. The design used in this research was a quasi-experimental, non-equavalent control group design consisting of 1 group with a total of 30 pregnant women as respondents. The intervention was given for 7 days to pregnant women. Nausea and vomiting were measured before and after intervention using the Pregnancy Unique Quantification of Emesis and Nausea (PUQE)-24 questionnaire. The test used in the bivariate analysis was the Wlcoxon test statistical test. The research results showed that giving lemon aromatherapy was effective in reducing nausea and vomiting in pregnant women. It can be concluded from this research that giving lemon aromatherapy is effective in reducing nausea and vomiting in first trimester pregnant women. Keywords: Lemon Aromatherapy, Nausea Vomiting, Pregnant Mother  ABSTRAK Emesis gravidarum merupakan  mual  muntah yang   muncul pada   empat   minggu   pertama kehamilan   dan   perlahan   menghilang   pada umur  kehamilan  menginjak  dua  belas  minggu. Mual  dan  Muntah  adalah  gejala  yang  paling  umum  dialami  oleh  wanita  hamil pada  trimester  pertama,  gejala   ini   dialami  oleh  70-85%  wanita. Untuk melihat Pengaruh Aromaterapi Lemon Terhadap Mual Muntah Pada Ibu Hamil Trimester I Di Wilayah Kerja Bebesan. Desain yang digunakan dalam penelitian ini adalah Quasi eksperimen, non equavalen control group design yang terdiri dari 1 kelompok dengan jumlah rensponden sebanyak 30 ibu hamil. intervensi diberikan selama 7 hari pada ibu hamil. Mual muntah diukur sebelum dan sesudah intervensi dengan menggunakan kuesioner Pregnancy Unique Quantification of Emesis and Nausea (PUQE)-24. Uji yang digunakan pada analisis bivariat dengan uji statistik wlcoxon test. Hasil penelitian didapat pemberian aromaterapi lemon efektif terhadap penurunan mual muntah pada ibu hamil. Dapat disimpulkan penelitian ini yaitu pemberian aromaterapi lemon efektif terhadap penurunan mual muntah pada ibu hamil trimester I. Kata Kunci: Aromaterapi Lemon, Mual Muntah, Ibu Hamil